STRATEGI BAURAN PROMOSI UNTUK MENINGKATKAN PREFERENSI KONSUMEN PADA TOKO RITEL YANG BERORIENTASI - MACHDI, ALAN (Universitas Katolik Widya Mandala Surabaya, 2012)
Promotion Mix Strategy is a strategy used by retailers to provide information, influence and communicate their brand message to consumers or aims to achieve its marketing objectives in the target market. Sales promotion mix strategies are applied retailers (Promotion mix) includes several things, among others. personal selling, advertising, sales promotion, public relations and publicity. The purpose of this section to find out which type of campaign is best suited to attract the attention of consumers through the Sales Promotion Mix Strategy (Promotion Mix) and to know the strategy of Sales Promotion Mix (Promotion Mix) which allows selected by retailers to attract and retain customers.